Effects of organic materials on dry matter econohic benefits of corn accumulation yield (Bangladesh Journal of Botany, 2024)
Field experiments were conducted using "Zhengdan 958" as the experimental material to study the effects of returning two different organic materials to the field on the dry matter accumulation, yield, and economic benefits of corn cultivation. Results indicate that straw and pig manure as organic materials both contribute to increasing the accumulation of dry matter and yield of corn. Comparatively, the effect of pig manure is more significant. At maturity, returning pig manure to the field can increase the accumulation of mature corn dry matter by 15.85%, yield by 21.93%, and economic benefits by 23.41%.Bangladesh J. Bot. 53(3): 697-701, 2024 (September) Special